Functional status, pain and return to work of injured motorcyclists involved in a motorcycle crash over one-year post-injury in Vietnam - Doan, Han Thi Ngoc; Hobday, Michelle; Leavy, Justine; Jancey, Jonine (2020)
© 2020 Elsevier Ltd